SARS-CoV-2 vaccine excipients polyethylene glycol and trometamol do not induce mast cell degranulation, in an in vitro model for non-IgE-mediated hypersensitivity - Quan, Paola Leonor; Ollé, Laia; Sabaté-Brescó, Marina; Guo, Yanru; Muñoz-Cano, Rosa; Wagner, Annette; Gastaminza, Gabriel; Martín, Margarita (Frontiers in Allergy, 2022)
The development of vaccines against SARS-CoV2 brought about several challenges in the management of hypersensitivity reactions to these vaccines. The search for the mechanisms involved in these adverse events initially focused on two excipients, polyethylene glycol, and trometamol, which may trigger activation responses by non-IgE mediated pathways. We sought to determine whether these components in pure form were capable of stimulating mast cells directly. To test this hypothesis, we used an in vitro model for non-IgE mediated activation that has previously shown degranulation responses mediated via MRGPRX2 with known drug agonists of the receptor. Human LAD2 mast cells were incubated with different concentrations (1 mg/mL, 10 mg/mL, 50 mg/mL) of Trometamol and of purified polyethylene glycol/Macrogol (molecular weights: 2000, 3350, 4000, and 6000). Mast cell degranulation was assessed using a beta-hexosaminidase read-out. Degranulation responses for all reagents tested showed no significant differences from those obtained from the negative control (basal degranulation). Purified PEG and trometamol did not induce MC degranulation in an in vitro model for the study of non-IgE mechanisms of drug hypersensitivity, previously shown to be useful in the study of MRGPRX2-mediated reactions. Studies using complete vaccine formulations, lipid conjugates, and receptor gene variants are needed to further clarify mechanisms of vaccine hypersensitivity.